Peach based horti-pastoral system of forage production on marginal land in Indian Himalaya - Yadav, R.P.; Bisht, J.K.; Mondal, T.; Meena, V.S.; Choudhary, M. (Indian Journal of Agroforestry, 2020)
Livestock rearing is an integral part of hill agriculture which plays vital role in Himalayan economy. Fruit trees are most favored plants in hills of Himalaya. The present investigation was carried out at experimental farm of ICAR-Vivekananda Parvatiya Krishi Anusandhan Sansthan, Hawalbagh, Almora, Uttarakhand. Peach trees were planted in 2007 at a spacing of3m × 6m,and the inter-space between trees was used for growing of different grasses. Treatment combinations included Setaria sphacelata (cv. Kajungula)/perennial rye, hybrid napier/tall fescue, broad-leaved paspalum/Hima-14 and congo-signal/grassland manava grasses grown under peach tree to utilize lying inter-space and in open conditions. The results revealed that pooled green forage (kharif+rabi) of grasses without peach (open) was 2.48% more than with peach tree, although it was non-significant. However, kharif grasses produced significantly higher green forage as compared to rabi grasses by 33.49% under peach and 56.6% without peach (open) situation. Among different grasses, S. sphacelata, perennial rye and their combination produced significantly higher green forage than rest grasses and their combinations. Likewise, gross return was two to five times more under peach as compared to without peach situation. Hence, farming community in the Himalayan region should introduce grasses under peach plantation to utilize the available space and generate more income through livestock rearing.